Canopy architectural and physiological characterization of near-isogenic wheat lines differing in the tiller inhibition gene tin - Moeller, Carina; Evers, Jochem B.; Rebetzke, Greg (Frontiers in Plant Science, 2014)
Tillering is a core constituent of plant architecture, and influences light interception to affect plant performance. Near-isogenic lines (NILs) varying for a tiller inhibition (tin) gene were investigated for tillering dynamics, organ size distribution, leaf area, light interception, red : far-red ratio, and chlorophyll content. Tillering ceased earlier in the tin lines to reduce the frequencies of later primary and secondary tillers, and demonstrated the genetically lower tillering plasticity of tin compared to free-tillering NILs. The distribution of organ sizes along shoots varied between NILs. In tin lines, internode elongation commenced at a lower phytomer, the peduncles were shorter, the flag leaves were larger, and the longest leaf blades were observed at higher phytomers. Total leaf area was reduced in tin lines. The tiller economy (ratio of seed-bearing shoots to numbers of shoots produced) was 10% greater in the tin lines (0.73-0.76) compared to the free-tillering sisters (0.62-0.63). At maximum tiller number, the red: far-red ratio (light quality stimulus that is thought to induce the cessation of tillering) at the plant-base was 0.18-0.22 in tin lines and 0.09-0.11 in free-tillering lines at levels of photosynthetic active radiation of 49-53% and 30-33%, respectively. The tin lines intercepted less radiation compared to their free-tillering sisters once genotypic differences in tiller numbers had established, and maintained green leaf area in the lower canopy later into the season. Greater light extinction coefficients (k) in tin lines prior to, but reduced k after, spike emergence indicated that differences in light interception between NILs cannot be explained by leaf area alone but that geometric and optical canopy properties contributed. The characterisation of specifically-developed NILs is refining the development of a physiology-based model for tillering to enhance understanding of the value of architectural traits for use in cereal improvement.